2000
DOI: 10.1080/00984100050136571
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Arsenic, Cadmium, Copper, Lead, Mercury, and Zinc in Human Placentas From Two Cities in Ukraine

Abstract: Ukraine is a highly industrialized country with major environmental problems and deteriorating reproductive health. Heavy metals are known reproductive toxins; a study was undertaken to determine whether they were present at sufficient concentrations to be playing a major role in these health problems. Placental concentrations of arsenic, cadmium, copper, lead, mercury, and zinc were determined in 200 women from the general population of two urban areas of Ukraine, Kyiv and Dniprodzerzhinsk. Arsenic was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Hg concentrations varied widely; the highest were found in China (Shanghai) and Japan (Suzuki et al 1984; Tsuchiya et al 1984; Yang et al 1997), where the mean exceeded 50 ng/g, and in the Faroe Islands, with a median of approximately 90 ng/g (Needham et al 2011). In contrast, in Germany (Schramel et al 1988) and the Ukraine (Zadorozhnaja et al 2000), most samples were < LOD. Three studies also provided the proportion of organic to inorganic Hg (Capelli et al 1986; Soria et al 1992; Suzuki et al 1984).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hg concentrations varied widely; the highest were found in China (Shanghai) and Japan (Suzuki et al 1984; Tsuchiya et al 1984; Yang et al 1997), where the mean exceeded 50 ng/g, and in the Faroe Islands, with a median of approximately 90 ng/g (Needham et al 2011). In contrast, in Germany (Schramel et al 1988) and the Ukraine (Zadorozhnaja et al 2000), most samples were < LOD. Three studies also provided the proportion of organic to inorganic Hg (Capelli et al 1986; Soria et al 1992; Suzuki et al 1984).…”
Section: Resultsmentioning
confidence: 96%
“…Some researchers have reported an absence of association with drinking habits (Roels et al 1978), dental fillings (Hsu et al 2007), or tobacco abuse (Roels et al 1978). Some studies reported contradictory results related to residence in areas with industrial exposure (Karp and Robertson 1977; Zadorozhnaja et al 2000), whereas others found no differences between women living in rural and urban settings (Roels et al 1978; Truska et al 1989). Data on occupational exposures were equally sparse: One small study of Chinese women exposed to Hg at a lamp factory reported elevated placental levels (Yang et al 1997), yet we found no studies that had measured placental Hg levels among other occupationally exposed women, such as dentists or chloralkali plant workers.…”
Section: Resultsmentioning
confidence: 99%
“…16, 2329 Placental arsenic concentrations reported worldwide between 1976–2000 30 were on average 6 ng/g (range: 3–12 ng/g) (wet weight). More recently Jin et al 24 measured placental arsenic concentrations as part of a study of neural tube defects in a rural area of the Shanxi Province in northern China.…”
Section: Discussionmentioning
confidence: 99%
“…In a smaller study of arsenic concentrations in placental tissue from participants living close to a copper smelter in Bulgaria, 28 mean arsenic concentrations of 23 (± SD 21) ng/g were detected in placentas of participants living near the smelter (n=30), whereas an average of 7 (± SD 4) ng/g arsenic was measured in placental samples from those outside of the smelter area (N=15). Previous studies have been hindered by instrumental detection limits 23, 29 , whereas we had the advantage of using ICP-MS for ultra-trace arsenic detection. In light of our low detection limits and our findings of a range of placenta arsenic concentrations that extend below levels previously reported upwards to levels reported in industrially exposed communities, our study presents new information.…”
Section: Discussionmentioning
confidence: 99%
“…Cd is absorbed into human body through food, drink, inhalation and smoking. In addition to kidney, liver and bone, placenta is the main target organ where Cd accumulates [1]. One of the major sources of Cd hazard is occupational exposure.…”
Section: Introductionmentioning
confidence: 99%